Upaya Perlindungan Terhadap Anak dari Ancaman Kejahatan - Kasmanto Rinaldi (Asosiasi Dosen Akuntansi Indonesia, 2022)
Child is a girl or boy who are immature and have not yet experienced puberty. Child are the next generation for the nation, this causes children to be protected by their lives, so that they can grow and thrive and avoid violence and discrimination. This topic was chosen because children have physical and mental differences that are much different from adults so they are vulnerable to the threat of crime. The service method is carried out in stages, namely the preparation stage and the implementation stage. Every child must receive education on how to protect themselves from the threat of crime because crimes against children often occur and often damage children's psychology. The result is that children must know that there is legal protection provided by the state if they experience threats of crime. Therefore, this service activity aims to provide counseling or socialization in order to educate children on how to properly protect themselves from crime.